1999
DOI: 10.1046/j.1469-8137.1999.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone threshold doses and exposure–response relationships for the development of ozone injury symptoms in wild plant species

Abstract: The relative ozone sensitivities of 25 German native herbaceous plant species, representative of arable field margins or disturbed habitats, were examined over three consecutive growing seasons. Plants were grown from seed, potted into natural soils and exposed in open-top chambers for the entire season to different ozone-exposure regimes covering a range of concentrations from 5 to 48 ppb (seasonal 8 h daily mean). The assessment of ozone effects was carried out by recording the first day of visible sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 27 publications
4
44
1
Order By: Relevance
“…These types of disagreements in the sensitivity classifications when visible injury or growth-related parameters have been reported by many authors in the literature (see review by Davison and Barnes, 1998). It is worth noting the high sensitivity of the Trifolium species involved in the study, in agreement with Nebel and Fuhrer (1994), Nussbaum et al (1995), Karlsson et al (1995), Balls et al (1996), Ashmore et al (1996), Bergmann et al (1999) and Gimeno et al (2004). Since the ecology of these Trifolium species is quite different, Bergmann et al (1999) suggested that their great sensitivity could be related to evolutionary and genetic features.…”
Section: Ozone Effects On Species Of the Leguminosae Familysupporting
confidence: 75%
“…These types of disagreements in the sensitivity classifications when visible injury or growth-related parameters have been reported by many authors in the literature (see review by Davison and Barnes, 1998). It is worth noting the high sensitivity of the Trifolium species involved in the study, in agreement with Nebel and Fuhrer (1994), Nussbaum et al (1995), Karlsson et al (1995), Balls et al (1996), Ashmore et al (1996), Bergmann et al (1999) and Gimeno et al (2004). Since the ecology of these Trifolium species is quite different, Bergmann et al (1999) suggested that their great sensitivity could be related to evolutionary and genetic features.…”
Section: Ozone Effects On Species Of the Leguminosae Familysupporting
confidence: 75%
“…For this reason, ozone concentrations reached maximum values exceeding 110 ppb during for hours (Figure 7). researchers for crops with wide leaves when these are exposed to high ozone levels [2,3,6,7] . The typical damage is irregular, bifacial, marginal and intervein, with necrotic areas, whitish dots, and chlorotic in aged leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Some research works about exposure of plants from different communities at realistic levels of ozone have been reported, to assess the sensitivity of specific species to this pollutant to determine threshold values of damage and to propose secondary standards for protection to the vegetation [1,6,7,10,17].…”
Section: Introductionmentioning
confidence: 99%
“…We can therefore compare ozone sensitivity between species using visible injury, growth change induced by ozone, and antioxidant activity (Heath [9], Sheng et al [18], Bergmann et al [3], Bungener et al [5]). Recently there have been many studies conducted to determine plant response to ozone, but the physio-biochemical response to ozone may be expressed in complicated ways, and thus it may difficult to determine the exact relationship between ozone and plant growth.…”
Section: Introductionmentioning
confidence: 99%